(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Environmental apps and digital reporting tools are increasingly used to support environmental management in Australia, yet research remains fragmented across citizen science, digital government, technology adoption and environmental governance. This paper develops an integrated conceptual framework for digital environmental reporting in Australia through a systematic narrative review of 86 sources. The framework is conceptual and has not been empirically tested. It explains how four core constructs - digital tool characteristics, user behaviours, institutional settings and environmental outcomes - may be associated with the effectiveness of citizen-generated environmental reporting. The review identifies opportunities for improved monitoring coverage, transparency, operational efficiency, rapid detection of environmental harms and adaptive management. It also identifies challenges related to digital inequality, privacy, data governance, verification, institutional fragmentation, long-term maintenance, power, politics and Indigenous data sovereignty. Six propositions are advanced to guide future empirical research rather than to state causal findings. The paper contributes a governance-focused model that extends technology acceptance and digital government frameworks by situating environmental reporting within Australia's fragmented institutional context.